Challenges and Opportunities for Community Empowerment Practices in Indonesia during the Covid-19 Pandemic through Strengthening the Role of Higher Education - Arifin Saleh; Mujahiddin Mujahiddin (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Covid-19 began to appear at the end of 2019 and began to spread in January 2020 precisely in Wuhan City, China. The presence of this virus has successfully paralyzed all world activities from various sectors, ranging from education, business, politics, tourism and so forth. This condition does not only occur in Indonesia but also affects all countries in the world. Of the various problems that arise in the middle of the community, it is felt necessary to provide a form of community empowerment practice. The main objective is not only to overcome problems related to economic income, but also to make people have the ability to meet their physical, economic and social needs. The practice of community empowerment is not only understood as a change activity carried out from within individuals, communities or organizations but also requires support and encouragement from outside parties, especially support from institutions that have a role in empowerment practices. One of the many institutions that have a role in the implementation of community empowerment practices is the University or in other terms referred to as Higher Education. This research method uses a literature study approach which is a series of activities related to data collection techniques through literature, reading, recording and managing research material. The data taken in this literature study comes from the provision of online media, reference books and research journals that are considered relevant to be able to answer research questions. The results of this writing indicate that Higher Education has a role in the practice of community empowerment, both directly and indirectly through the implementation of Higher Education Tridharma. It's just that, in its implementation, the role of universities in the practice of community empowerment, especially during the Pandemic Covid-19 period is not as simple as imagined. Although there are opportunities in implementing empowerment practices, of course there are also forms of challenges that will be faced by universities in implementing community empowerment practices. Therefore, at least a strategic policy step from the central government is needed that can strengthen the role of Higher Education, as well as to answer the Challenges and Opportunities for Community Empowerment Practices during the Pandemic Covid-19 Through the Role of Higher Education.